Samples collected from the floor of Jezero crater with the Mars 2020 Perseverance rover - Simon,JI; HickmanLewis,K; Cohen,BA; Mayhew,LE; Shuster,DL; Debaille,V; Hausrath,EM; Weiss,BP; Bosak,T; Zorzano,M; Amundsen,HEF; Beegle,LW; et al. (Journal of Geophysical Research: Planets, 2023)
The first samples collected by the Mars 2020 mission represent units exposed on the Jezero Crater floor, from the potentially oldest Séítah formation outcrops to the potentially youngest rocks of the heavily cratered Máaz formation. Surface investigations reveal landscape-to-microscopic textural, mineralogical, and geochemical evidence for igneous lithologies, some possibly emplaced as lava flows. The samples contain major rock-forming minerals such as pyroxene, olivine, and feldspar, accessory minerals including oxides and phosphates, and evidence for various degrees of aqueous activity in the form of water-soluble salt, carbonate, sulfate, iron oxide, and iron silicate minerals. Following sample return, the compositions and ages of these variably altered igneous rocks are expected to reveal the geophysical and geochemical nature of the planet’s interior at the time of emplacement, characterize martian magmatism, and place timing constraints on geologic processes, both in Jezero Crater and more widely on Mars. Petrographic observations and geochemical analyses, coupled with geochronology of secondary minerals, can also reveal the timing of aqueous activity as well as constrain the chemical and physical conditions of the environments in which these minerals precipitated, and the nature and composition of organic compounds preserved in association with these phases. Returned samples from these units will help constrain the crater chronology of Mars and the global evolution of the planet’s interior, for understanding the processes that formed Jezero Crater floor units, and for constraining the style and duration of aqueous activity in Jezero Crater, past habitability, and cycling of organic elements in Jezero Crater.